Escolas multisseriadas e os ideários pedagógicos: um estudo sobre as escolas do e no campo na região do Bico do Papagaio - Nunes, Klivia de Cássia Silva (2018)
This thesis aims to analyze the educational conceptions into teachers` practice in multigrade schools an express the main idea called Por uma Educação do Campo acording to educational policy to this modality teaching. As a teorical reference this study is based on Historical-Critical Pedagogy, whose the espitemological focus are reaseoned onto a marxist theory, which get a possibility to perceive the pedagogical process under the education goal. The main question used to carry out this research is: In what extend the educational practice of multigrade teachers assumes and express the conceptions of education that are present in the educational policies, delivered to the rural education? The hypotheses are: 1. The practice of rural teachers are based on a different approach from the conception Por uma Educação do Campo and founded on educational policy. However, both teacher`s practice and educational policy, follow the neoliberalism support, contributing to make fragile the struggle of the workers that living in rural area; 2. The historical-critical pedagogy theory, support that people must have access to the scientific knowledge made historically by humanity and in a unique education, in terms of contribute to personal development in a critical way and become aware of the need of social transformation . This idea presents as a choice to overcome the proposals based on neoliberalism orign. The main idea is that teachers working in multigrade class do not understand the educational theory as the Historical-Critical Pedagogy or even By a Field Education conception in a way that enables them to make it in practice. The reseach was conducted in rural schools with multigrade class in two cities at the Papagaio Beak / TO area: Tocantinópolis and Araguatins. The reseach methods used were the bibliografic reseach, documentary reseach, locus reseach, focus group, interview ans questionary. Through the research, it was found that by following the educational policy made official by the State, these cities obey the prerogatives put in the official documents that were made based on international agreements that are based on the Jacques Delors` report of the United Nations on education for the 21st century. However, the multigrade teachers` practices in schools present a gap of knowledge of the pedagogical conceptions into the the official recommendation and the ideals of Por uma Educação no Campo, nevertheless it contributing to the ideological project of the dominant social class, even in an unintentional way. Its makes evident that both pedagogical practice and rural educational policy follow the neoliberalism origin making fragile the awareness for the rural worker in terms of overcome the class society.